English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-10 19:10:52 · 7 answers · asked by alex 1 in Science & Mathematics Mathematics

7 answers

3 = 9x - 2x
3 = 7x
x = 3/7

2007-10-10 19:14:57 · answer #1 · answered by SVAL 4 · 1 0

Take the 9x and subtract by 2x leaving 7x
7x =3 therefore ansywer = 3/7

2007-10-11 02:16:08 · answer #2 · answered by ThE RiDdLeR 3 · 0 1

First put variables in a side and other constants in other side
2x-9x = -3
-7x = -3
7x = 3
x = 3 / 7

2007-10-11 10:35:09 · answer #3 · answered by Rayan Ghazi Ahmed 4 · 0 0

Move the terms with (x) one side of (=) and the terms without (x), the other side
2x-9x=-3 When you move a term the other side of (=) you have to change the sign ... + becomes - and - becomes +

-7x=-3

x=3/7

2007-10-11 02:40:01 · answer #4 · answered by Anonymous · 0 0

2x + 3 = 9x
-2x = 9x-2x

3 = 7x

x = 3/7

2007-10-11 02:14:43 · answer #5 · answered by Sandra R 1 · 1 1

3 = 7 x
x = 3 / 7

2007-10-11 03:15:52 · answer #6 · answered by Como 7 · 0 0

3=7x
x=7/3

2007-10-11 02:14:23 · answer #7 · answered by katia 1 · 1 3

fedest.com, questions and answers